1987
DOI: 10.1103/physrevb.35.3675
|View full text |Cite
|
Sign up to set email alerts
|

Multilayer phase diagram ofCF4adsorbed on graphite

Abstract: Layer transitions in CF4 adsorbed on graphite are studied by vapor-pressure isotherm measurements in the range one to eight layers and 52 K & T & 104 K, using an ellipsometric technique to measure the coverage on a single surface. A maximum of two layers adsorb below 71 K. Above 71 K we observe for the first time the condensation of a double-layer (third and fourth), which splits into separate layers above a triple point at 75 K. The fifth layer appears at 80 K, the sixth at 87 K, and at least eight discrete l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

1988
1988
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 37 publications
0
9
1
Order By: Relevance
“…The rare gases Ar, , Kr, and Xe 8,9 show complete wetting in both the liquid and solid states. For all other (nonspherical) molecules such as CF 4 and C 2 H 4 a first-order wetting transition has been observed which coincides with the triple point of the bulk system. Carbon monoxide also falls into this class even though wetting does not appear at the liquid−solid transition but at the triple point connected with the structural α−β transition of the bulk system .…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations
“…The rare gases Ar, , Kr, and Xe 8,9 show complete wetting in both the liquid and solid states. For all other (nonspherical) molecules such as CF 4 and C 2 H 4 a first-order wetting transition has been observed which coincides with the triple point of the bulk system. Carbon monoxide also falls into this class even though wetting does not appear at the liquid−solid transition but at the triple point connected with the structural α−β transition of the bulk system .…”
Section: Introductionmentioning
confidence: 73%
“…This means that Freon-114 belongs to the group of molecules that show triple-point wetting on graphite. [10][11][12]15 However, unlike CF 2 Cl 2 , the molecule C 2 F 4 Cl 2 does not show metastability and irregular fluctuations in the vicinity of the wetting transition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that CF 4 on graphite has a complex phase diagram in both the monolayer 5-7 and the multilayer regimes. 8,9 The monolayer phase diagram proposed by Zhang et al 7 is reproduced in Fig. 1.…”
Section: Introductionmentioning
confidence: 96%